Effect of cumulative seismic damage and corrosion on the life-cycle cost of reinforced concrete bridges. - Kumar, R. (Earthquake engineering & structural dynamics.)
Bridge design should take into account not only safety and functionality, but also the cost effectiveness of investments throughout a bridge life-cycle. This paper presents a probabilistic approach to compute the life-cycle cost (LCC) of corroding reinforced concrete (RC) bridges in earthquake-prone regions. The approach is developed by combining cumulative seismic damage and damage associated with corrosion due to environmental conditions. Cumulative seismic damage is obtained from a low-cycle fatigue analysis. Chloride-induced corrosion of steel reinforcement is computed based on Fick's second law of diffusion. The proposed methodology accounts for the uncertainties in the ground motion parameters, the distance from the source, the seismic demand on the bridge, and the corrosion initiation time. The statistics of the accumulated damage and the cost of repairs throughout the bridge life-cycle are obtained by Monte-Carlo simulation. As an illustration of the proposed approach, the effects of design parameters on the LCC of an example RC bridge are studied. The results are valuable in better estimating the condition of existing bridges and, therefore, can help to schedule inspection and maintenance programs. In addition, by taking into consideration the two deterioration processes over a bridge life-cycle, it is possible to estimate the optimal design parameters by minimizing, for example, the expected cost throughout the life of the structure. A comparison between the effects of the two deterioration processes shows that, in seismic regions, the cumulative seismic damage affects the reliability of bridges over time more than the corrosion even for corrosive environments.